Laparoscopic de-roofing of liver cyst with biliary communication, success or failure: case report - Pant, Priyanka; Basak, Samindra Nath (International Surgery Journal, 2020)
A 39 year old gentleman complained of right upper abdominal pain. Ultrasonography revealed cholelithiasis with a cystic space occupying lesion in liver of around 14 cm. Computed tomograpy of whole abdomen was done which revealed a cystic lesion of 14.1×10.6×12.4 cm dimensions in right lobe of liver suggestive of simple cyst. Laparoscopic cholecystectomy was done along with de-roofing of cyst wall, bile leak was noted from a tiny orifice which was found communicating with biliary system by intraoperative cholangiography. Primary closure of opening done by suturing laparoscopically. Patient did well postoperatively and followed for 2 years with no complications and/or recurrence.A 39 year old gentleman complained of right upper abdominal pain. Ultrasonography revealed cholelithiasis with a cystic space occupying lesion in liver of around 14 cm. Computed tomograpy of whole abdomen was done which revealed a cystic lesion of 14.1×10.6×12.4 cm dimensions in right lobe of liver suggestive of simple cyst. Laparoscopic cholecystectomy was done along with deroofing of cyst wall, bile leak was noted from a tiny orifice which was found communicating with biliary system by intraop cholangiography. Primary closure of opening done by suturing laparoscopically. Patient did well postoperatively and followed for 2 years with no complications and/or recurrence. A 39 year old gentleman complained of right upper abdominal pain. Ultrasonography revealed cholelithiasis with acystic space occupying lesion in liver of around 14 cm. Computed tomograpy of whole abdomen was done whichrevealed a cystic lesion of 14.1×10.6×12.4 cm dimensions in right lobe of liver suggestive of simple cyst. Laparoscopiccholecystectomy was done along with de-roofing of cyst wall, bile leak was noted from a tiny orifice which was foundcommunicating with biliary system by intraoperative cholangiography. Primary closure of opening done by suturinglaparoscopically. Patient did well postoperatively and followed for 2 years with no complications and/or recurrence.